2014
DOI: 10.1016/j.joca.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and association of osteoarthritis with fracture risk

Abstract: Women with OA have an increased risk of fragility fracture, and the risk was mainly observed in non-osteoporotic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 39 publications
(35 reference statements)
3
22
0
Order By: Relevance
“…Fall history and knee OA (vs. neither or only one) was associated with worse KOOS-QoL and SF12 Physical Component Summary scores, in persons with or at higher risk for knee OA in the Osteoarthritis Initiative (19). Fracture risk was higher in women with OA (Dubbo Osteoporosis Epidemiology Study) than those without OA; however, the association was mainly observed in women with osteopenic BMD (for vertebral and limb fracture, but not hip fracture) and normal BMD and not in those with osteoporosis (20). …”
Section: Resultsmentioning
confidence: 98%
“…Fall history and knee OA (vs. neither or only one) was associated with worse KOOS-QoL and SF12 Physical Component Summary scores, in persons with or at higher risk for knee OA in the Osteoarthritis Initiative (19). Fracture risk was higher in women with OA (Dubbo Osteoporosis Epidemiology Study) than those without OA; however, the association was mainly observed in women with osteopenic BMD (for vertebral and limb fracture, but not hip fracture) and normal BMD and not in those with osteoporosis (20). …”
Section: Resultsmentioning
confidence: 98%
“…This would explain the occurrence of a dislocation instead of a femoral neck fracture and, also, the occurrence of a pure dislocation, i.e., not accompanied by any fracture of the acetabulum. However, the clinical correlation between hip osteoarthritis and fracture of the proximal femur remains controversial [16][17][18][19]. Finally, some suggested that a low anteversion of the proximal femur or even a retroversion would favor a traumatic hip dislocation [3,20].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the combination of osteoarthritis and osteoporosis in the occurrence of fractures has been reported in the prospective dubbo osteoporosis epidemiology study [40]. As compared with individuals without osteoarthritis, individuals with self-reported osteoarthritis were older, had higher BMI and BMD (in spine and femoral neck) and more frequently a recent fall.…”
Section: Bmd-bmi Interaction In Osteoarthritismentioning
confidence: 95%
“…Earlier studies [49,50] have indicated that a large proportion of patients awaiting total arthroplasty of the hip or knee because of osteoarthritis also have osteoporosis. An interesting finding of the Australian study [40] is that one out of five women and men with osteoporosis had self-reported osteoarthritis. In these patients with osteoporosis, fracture risk was similar between patients with and without osteoarthritis.…”
Section: Do Osteoporosis and Osteoarthritis Coexist?mentioning
confidence: 99%